Evaluation of the auxiliary diagnostic value of antibody assays for the detection of novel coronavirus (SARS‐CoV‐2). Issue 10 (11th July 2020) - Yong, Gao; Yi, Yuan; Tuantuan, Li; Xiaowu, Wang; Xiuyong, Li; Ang, Li; Mingfeng, Han
Abstract: The spread of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) has taken on pandemic proportions, affecting over 100 countries in a matter of weeks. The goal of this study was to assess the diagnostic values of different methods of detecting and estimating the SARS‐CoV‐2 infection, and the auxiliary diagnostic potential of antibody assays. By retrospectively analyzing the data of viral RNAs and serum immunoglobulin M‐immunoglobulin G antibodies against SARS‐CoV‐2 from 38 cases with confirmed coronavirus disease 2019 in the Second People's Hospital of Fuyang, we found that, in the early phase of the illness, the viral RNA was most abundant in the sputum specimens, followed by that in the throat swabs, while the antibody assays identified fewer positive cases at this stage. However, the sensitivity of the antibody assays overtook that of RNA test from the eighth day of disease onset. Simultaneous use of antibody assay and reverse transcription‐quantitative real‐time polymerase chain reaction improved the sensitivity of the diagnoses. Moreover, we found that most of these cases with no detectable viral RNA load during the early stages were able to be seropositive after 7 days. Our findings indicate that the antibody detection could be used as an effective supplementary indicator of SARS‐CoV‐2 infection in suspected cases with no detectable viral RNA, and in conjunction with nucleic acid detection in confirming the infection.